Acetylcholinesterase Activity in certain Diseases - Muhammad, Shereen; Mabood, SF; Ullah, Asad; Ali, Akhtar (Journal of Postgraduate Medical Institute, 2011)
Activity of Acetylcholinesterase in certain disease like chronic renal failure (CRF), rheumatic heart diseases (RHD), hepatic jaundice (HJ) and heroin addiction (HA) was estimated in 300 patients. The michaelis menten parameterss (aKm and aVm) were used for the activity estimation. The enzyme activity was measured by following the yellow colour produced from thiocholine iodide (tch. I) reacting with 5,5 dithlobis 2 nitrobenzoate (DTNB). Results show low acetylcholinesterase activities in the disease state as compared to normal. activity estiamtion in them will help in understanding the disease process.